Solid phase extraction for sample clean-up of oil spill samples - Lee, Luen Ee, 1988-; Umi Kalthom Ahmad, supervisor; Fakulti Sains (2010)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2010